MAPPING HRM IMPLEMENTATION IN INDONESIA’S SMES: IN SEARCH OF NEW HRM MODEL - Sapta Dwikardana; Angela Teressia (Faculty of Economics and Business, University of Pasundan, 2022)
In Indonesia, SMEs business owners are always trying to find the best employee management practices that suit their business scale, so finding a comprehensive employee management model for SMEs is important. This research was conducted using a qualitative approach. Data collection was carried out using semi-structured interviews with 38 managers who were directly involved in HRM in SMEs. The analytical method used is content and thematic analysis. The results of this study offer new insights for SME owners regarding HRM practices that can be applied to systematically manage their human resources to increase their competitiveness. The novelties of this research are (a) This research was conducted for more comprehensive employee management functions where most of the previous studies were based on certain functions only; (b) a special SME HR model that can be used as a standard for SMEs in Indonesia.